2013
DOI: 10.15381/anales.v69i4.1125
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotección antioxidante de la cáscara y semilla de Vitis vinifera L. (uva)

Abstract: Resumen Objetivo: Determinar la capacidad hepatoprotectora antioxidante, inducida por las semillas y cáscaras de la uva Vitis vinifera L., en animales de experimentación con agresión alcohólica, mediante la prueba del TBARS (sustancias reactivas al ácido tiobarbitúrico). Diseño: Estudio experimental. Institución: Centro de Investigación de Bioquímica y Nutrición Alberto Guzmán Barrón, Facultad de Medicina, Universidad Nacional Mayor de San Marcos, Lima, Perú. Material biológico: Ratones albinos, machos, adulto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
0
3
0
5
Order By: Relevance
“…Esta citoprotección se debe en gran medida a los polifenoles, que son parte constituyente de la cáscara y pulpa de la papa y cuyo rol es limpiar de los radicales libres al producto y mantenerlo en buen estado de conservación (22) . Al igual que otros productos vegetales, como frutas y verduras, su concentración y capacidad funcional dependen del grado de maduración (23) .…”
Section: Discussionunclassified
“…Esta citoprotección se debe en gran medida a los polifenoles, que son parte constituyente de la cáscara y pulpa de la papa y cuyo rol es limpiar de los radicales libres al producto y mantenerlo en buen estado de conservación (22) . Al igual que otros productos vegetales, como frutas y verduras, su concentración y capacidad funcional dependen del grado de maduración (23) .…”
Section: Discussionunclassified
“…Silymarin is an active principle that possesses hepatoprotector and regenerative action; its mechanism of action derives from its capacity to counterarrest the action of FR, which are formed due to the action of toxins that damage the cell membranes (lipid peroxidation), competitive inhibition through external cell membrane modification of hepatocytes; it forms a complex that impedes the entrance of toxins into the interior of liver cells and, on the other hand, metabolically stimulates hepatic cells, in addition to activating RNA biosythesis of the ribosomes, stimulating protein formation. In a study published by [41], the authors observed that silymarin's protector effect on hepatic cells in rats when they employed this as a comparison factor on measuring liver weight/animal weight % (hepatomegaly), their values always being less that those of other groups administered with other possibly antioxidant substances; no significant difference was observed between the silymarin group and the silymarin-alcohol group, thus demonstrating the protection of silymarin. On the other hand, silymarin diminishes Kupffer cell activity and the production of glutathione, also inhibiting its oxidation.…”
Section: Antioxidant and Hepatoprotector Actionmentioning
confidence: 99%
“…In general, it possesses functions such as its antioxidant one, and it can diminish hepatic damage because of its cytoprotection as well as due to its inhibition of Kupffer cell function. [41].…”
Section: Silimarina (Silybum Marianum)mentioning
confidence: 99%
“…Grape juice has also shown to protect against alcohol intoxication by inhibiting production of ethanol-induced free radicals [84]. The active components present in grape juice and grape seed extract Vitis vinifera L. are flavonoids, such as catechins, epicatechins, anthocyanidins, proanthocyanidins, and resveratrol [85,86].…”
Section: Plant Extracts and Plant Concoctionsmentioning
confidence: 99%